2009
DOI: 10.1007/s12588-009-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and flammability behavior of PP/ banana and glass fiber-based hybrid composites

Abstract: Hybrid composites of polypropylene (PP) reinforced with short banana and glass fi ber were fabricated using melt-blending technique followed by injection molding. Maleic anhydride grafted polypropylene (MAPP) has been used as a coupling agent to promote the interfacial adhesion between the fi bers and the PP matrix. The degradation behavior in the composites and hybrid composites were studied employing FTIR spectroscopy. Test results indicated an increase in the carbonyl and hydroxyl regions increase with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, the extent of degradation was dependent on the level of exposure to irradiation with higher exposure resulting in greater weight loss (%). Limiting oxygen index data showed that banana glass polypropylene composites had lower burning rate than the banana polypropylene composites .…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the extent of degradation was dependent on the level of exposure to irradiation with higher exposure resulting in greater weight loss (%). Limiting oxygen index data showed that banana glass polypropylene composites had lower burning rate than the banana polypropylene composites .…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 94%
“…Treating the banana fibers with alkali or benzoylation leads to substantial improvement in properties, due to enhanced fiber distribution. Banana and glass fiber were also used to develop hybrid composites with polypropylene and the biodegradation and thermal behavior were investigated . Based on the weight loss after degradation in soil, it was observed that the banana fibers had considerably higher degradation (weight loss) than the glass fiber reinforced composites.…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 99%
“…In this context, hybrid composites are the greatest option for structural‐related utilizations. Glass fiber was frequently hybridized with different natural fibers that is, jute, [ 32–35 ] sisal, [ 33–36 ] kenaf, [ 37,38 ] , banana, [ 39,40 ] flax, [ 41 ] and hemp [ 42 ] to improve their mechanical properties. Additionally, different natural fibers of relatively low modulus and high elongation were also hybridized with other natural fibers to improve their properties that is, flax/jute, [ 43 ] banana/sisal, [ 44 ] kenaf/flax, [ 45 ] kenaf/pineapple leaf, [ 46 ] basalt/hemp, [ 47 ] and so on.…”
Section: Introductionmentioning
confidence: 99%